Базові положення концепції Inbound маркетингу в період соціалізації суспільства. (Economics and region, 2022)
In the period of transformation and adaptation to the digital economy, a new marketing approach in the system of joint value creation, namely inbound marketing, is becoming increasingly important. It is proved that inbound marketing is spreading among business entities due to cost reduction and increase in economic performance of the enterprise. The effectiveness of inbound marketing is explained by the constantly growing role of the interconnectedness factor, which significantly affects the communication interaction between the stakeholders of the business entity (customers, employees, trading partners and government officials), each of whom is a direct or potential consumer of goods and services offered by the company. The article investigates the definition of the essence of the concept of "inbound marketing" from the point of view of foreign and domestic scientists, offers its own definition, which forms the mechanism of action of the concept of inbound marketing, which is integrated into the activities of the enterprise. Inbound marketing as an integrated system today uses all available tools and technologies of project management, promotion of resources and advertising from the very beginning of the project to daily tactical tasks and summarizing. To form the concept of inbound marketing, modern principles of its mechanism implementation were analyzed and own principles were proposed that will expand and diversify marketing activities, increase its efficiency and effectiveness, as well as reduce unnecessary tangible (monetary) and intangible (time) marketing costs by increasing consumer loyalty to enterprises that carry out transparent economic and social activities, as well as reducing the time for making managerial decisions on the formation of marketing tactics and the use of tools and technologies. For the most effective construction of the concept of inbound marketing, its advantages and disadvantages were analyzed, which are proposed to be overcome by a number of actions of the company's management.
Keywords: marketing; inbound marketing; essence; principles; tools; digitalization; lead